Discipline as a determinant of school performance: A case of junior high school in Namibia - Shonena, Helvi Frieda; Haufiku, Isidor (UIN Raden Mas Said Surakarta, 2023)
Successful teaching and learning can only take place in schools when there is positive discipline. Lack of discipline is called indiscipline. Thus, indiscipline can be regarded as any learners’ action that is deemed to be wrong and not generally accepted as proper in a set up or society. This shows that discipline is critical for learners ‘good academic performance. Therefore, this study was conducted to investigate how discipline enables academic performance in Junior Secondary Schools at Katjinakatji Circuit in the Kavango West region, Namibia. The study aimed to determine the causes of indiscipline, assess how discipline enables academic performance and find measures school administrators can use to deal with indiscipline among learners. The study used a mixed research method to collect data from 48 participants comprises of,3 Principals, 15 teachers and 30learnerswho are currently teaching and schooling at the three selected Junior Secondary Schools in the study area. Participants were selected using simple random sampling and purposive sampling methods. Data was collected using questionnaires and interview guides. The study established that negligent parents contributed to indiscipline in the Katjinakatji circuit. Results show that disciplined learners are likely to perform better, unlike indiscipline learners. Measures to be taken by school administrators to ensure discipline are time management, punishment, and reinforcement of school rules and regulations.